Who Are These Workers, Anyway?. Issue 1 (23rd March 2016) - Griggs, Tracy L.; Eby, Lillian T.; Maupin, Cynthia K.; Conley, Kate M.; Williamson, Rachel L.; Griek, Olivia H. Vande; Clauson, Muriel G.
Abstract : The focal article by Bergman and Jean (2016 ) raises an important issue by documenting the underrepresentation of nonprofessional and nonmanagerial workers in industrial and organizational (I-O) research. They defined workers as, "people who were not executive, professional or managerial employees; who were low- to medium-skill; and/or who were wage earners rather than salaried" (p. 89). This definition encompasses a wide range of employee samples: from individuals working in blue-collar skilled trades like electricians and plumbers to police officers, soldiers, and call center representatives to low-skill jobs such as fast food, tollbooth operators, and migrant day workers. Because there is considerable variability in the pay, benefits, skill level, autonomy, job security, schedule flexibility, and working conditions that define these workers' experiences, a more fine-grained examination of who these workers are is necessary to understand the scope of the problem and the specific subpopulations of workers represented (or not) in existing I-O research.